Glycolysis in gastrointestinal stromal tumor: a brief overview - Takafumi Shima; Kohei Taniguchi; Yosuke Inomata; Jun Arima; Sang-Woong Lee (Neoplasia: An International Journal for Oncology Research, 2024)
Gastrointestinal stromal tumor (GIST) is the most prevalent mesenchymal tumor of the digestive tract. Its growth is primarily influenced by mutations in KIT or PDGFRA. Surgery is the primary treatment option for GIST; however, KIT inhibitors, such as imatinib, are used for inoperable cases. Resistance to imatinib is an upcoming challenge, especially because the effectiveness of alternative drugs is limited. Enhancement of the glycolysis pathway in cancer cells has been identified as a key feature in cancer. This unique metabolic activity has implications on tumor growth, prognosis, and resistance to therapy, even in GIST. Members of the glucose transporter (GLUT) family (particularly GLUT-1) play a significant role in GIST progression and response to treatment. Diagnostic imaging using 18F-fluorodeoxyglucose positron emission tomography/computed tomography, which enables visualization of glucose metabolism, can aid in GIST diagnosis and risk assessment. The interplay between glycolysis and GIST can lead to the development of various therapeutic strategies, especially those involving glycolysis-related molecules, such as hexokinase and lactate dehydrogenase. However, further research is required to understand the full spectrum of glycolysis in GIST and its therapeutic potential. Herein, we present an exhaustive overview and analysis of the role of glycolysis in GIST, especially as a therapeutic target.